PARENTING PATTERNS AND STUNTING EVENT RATE IN RANDUAGUNG VILLAGE, KEBOMAS DISTRICT, GRESIK REGENCY - Kurniawan, Freddy; Grace, Paulina Holy; Arjuna, Sansan Rollens; Cahyani, Ni Putu Novi; Raharja, Davin; Benevitto, Axel; Silva, Theodora Emanuella da; Aranda, Biembee Nayoan Cosa; Setiadi, Rocky; Hamdani, Delincia; Ekaristy, Mergivia; Winarjo, Givenchy Angela; Rihadi, Lukas Slamet; Wattimena, Inge; Sustini, Florentina; Wijono, Steven; Dewi, Dewa Ayu Liona; Sincihu, Yudhiakuari; Puspitasari, Dyan Eka (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2023)
Background: The high number of stunting cases in Randuagung Village, Kebomas District in Gresik Regency requires a case analysis to determine the risk factors for stunting, as well as the relationship between parenting and the risk of stunting in Randuagung Village in an effort to properly overcome this stunting cases.Purpose: The purpose of this study was to analyze the association between parenting in children and the incidence of stunting in Randuagung Village, Kebomas District in Gresik Regency.Method: This research is an analytical study with a case control research design which is a form of observational study that has the aim of analyzing the association between the incidence of stunting (dependent variable) and the type of parenting (independent variable) in Randuagung Village, Kebomas District in Gresik Regency.Result: The results of a study of 85 respondents conducted in April 2022 concluded that there was an association between parenting in children and the incidence of stunting in Randuagung Village, Kebomas District, Gresik Regency. Conclusion: There is an association between parenting in children and the incidence of stunting in Randuagung Village, Kebomas District, Gresik Regency.